Les étudiants indigènes dans l'enseignement supérieur au Chili - María Elena González Plitt (Les éditions de la Maison des sciences de l'Homme, 2008)
This article analyzes the situation of the indigenous students, specifically Mapuche students, who have enrolled at an institution of higher education in Chile, specifically at Universidad de La Frontera (UFRO). This analysis is made by emphasizing three dimensions: 1) The situation of access and permanence of indigenous students at the university. 2) The results of a of an affirmative action program, established since 2004, oriented to support both, Mapuche students' academic training, and the strengthening of their cultural identity. 3) The interaction between the knowledge from of their university training and their vernacular knowledge. We end the article by discussing the challenges and needs these kings of reality demands from the universities and the Mapuche society, mainly from the perspective of redefining the relationships and expectations of the various actors who converge in the educational system. The latter, in order to rethink and redesign the current policies and practices, in order to achieve real equity and to construct an epistemological and intercultural dialog that may help overcome mutual mistrust, and academic paternalism and ethnocentrism in the field of higher education.